THE ROLE OF THE BULELENG DISTRICT DEPARTMENT OF INDUSTRY, TRADE, COOPERATIVES AND SMEs IN PROVIDING LEGAL PROTECTION OF THE INTELLECTUAL PROPERTY RIGHTS OF MSME ENTERPRISES IN BULELENG DISTRICT, BALI - Evan Rezky Saragih; Muhamad Jodi Setianto; Ni Luh Wayan Yasmiati (PT. Antis International Publisher, 2024)
This research investigates the role of the Buleleng Regency Industrial Trade and SME Cooperative Service in providing legal protection for the intellectual property rights (IPR) of MSME industry players in Buleleng Regency, and the obstacles faced in these efforts. Using empirical legal methods and non-probability sampling, the study involves the Department of Trade, Industry and Cooperatives, and MSME business actors. Data collection techniques include document study, observation, and interviews, with qualitative descriptive analysis. The findings reveal that the Department's role encompasses preventive measures like intensive outreach, IPR registration recommendations, technical guidance, and collective IPR registration facilitation, as well as repressive measures such as providing legal assistance during IPR violations. Obstacles include low awareness and understanding of IPR among MSME actors, the complexity of the registration process, limited competence of some employees, and an annual quota for IPR registration recommendations.